Effect of a Non-Hydrostatic Core-Mantle Boundary on Earth's and Mars'Rotational Dynamics - Folgueira-López, M. (2025)
Dynamic loads within planetary mantles can deform the core-mantle boundary (CMB). On Earth, subducting slabs primarily induce degree-2, order-2 deformation of the CMB, though additional degrees arise when expanded in spherical harmonics. Nutations, observed through Very Long Baseline Interferometry (VLBI), and variations in the Length of Day (LOD) are measured with high precision. While the first-order effect of Earth's nonhydrostatic flattening significantly contributes to nutation amplitudes, we focus here on second-order effects. We compute the pressure torque acting on an irregular CMB, which can perturb both nutations and LOD. For nutations, topographic effects are generally small, as they are proportional to the product of two topography coefficients, except in cases of resonance, where the tidal frequency is close to an inertial wave frequency. We identify three such cases, though none lead to nutation amplifications exceeding 2 microarcseconds. This finding definitely excludes topographic pressure as an efficient mechanism to explain nutations. For LOD, we find significant amplification near specific resonances: the tide at 13.633 days is quite close to an inertial wave at 13.614 days, and the tide at 27.555 days to an inertial wave at 27.666 days, both resulting in an amplification of 0.06 milliseconds, at the level of the observed residuals. We also assess the effects on Mars but find that its tidal and nutation frequencies do not come sufficiently close to the determined inertial wave frequencies, leading to negligible resonance effects.